The Practice of Local Wisdom-Based Literary Literacy in Language and Literature Learning at Junior High School of Ternate City - Adam, Samsudin Hi; Ali, Silvani Umar; Muahmmad, Hujaefa Hi; Marasabessy, Fachria; Soleha, Lilin Kartina (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Literature has a very strategic role in teaching cultural values to students since it contains values reflecting people's lives. However, along with the development of the globalization era, local culture has begun to disappear due to changes in people's lifestyles. Therefore, literary literacy based on local wisdom needs to be introduced to the younger generation as educational medium to build society with character. This study aims to explore the practice of local wisdom-based literary literacy in language and literature learning at Junior High School level in Ternate City. The study uses qualitative design involving language teachers (Indonesian and English Teachers). Data collection techniques are carried out through observation, inter-views, and documentation. The results indicate that the teachers have implemented local wisdom-based literary literacy in language and literature learning. The learning resources used by teachers are in the form of printed and non-printed learning re-sources. Printed learning resources used are books, magazines, and newspapers. While non-printed learning resources are in the form of Compact Disc, TV, YouTube, historical tours, nature tours, figures, heroes, and libraries. The teachers develop their own teaching materials by adopting local wisdom content taken from the regional library and downloaded from the internet because the school library does not provide literary books with stories about the local wisdom of North Maluku. The materials used include appreciation of poetry and folklores about local wisdom of North Maluku. The learning strategies are applied in three stages called before reading, when reading, and after reading. The results showed that literary literacy activities based in local wisdom values have been implemented by teachers, so the students can developing their characters.